Polyglycolic Acid Felt for Prevention of Frey Syndrome After Parotidectomy. Issue 4 (October 2018) - Aizawa, Tetsushi; Kuwabara, Masahiro; Kubo, Satoshi; Aoki, Shimpo; Azuma, Ryuichi; Kiyosawa, Tomoharu
Abstract : Background: Frey syndrome is one of the important complications of parotid surgery. Placing a barrier between the parotid gland and the skin flap is considered to be effective for preventing this syndrome by blocking misdirected regeneration of nerve fibers. Neoveil is nonwoven polyglycolic acid (PGA) felt that is used as absorbable reinforcing material. The present study evaluated the effectiveness of this PGA felt as a barrier for preventing Frey syndrome. Methods: A total of 19 patients who underwent superficial parotidectomy from 2012 to 2017 were retrospectively reviewed. Application of PGA felt (n = 9) or sternocleidomastoid flap (SCMF) transfer (n = 10) was performed to prevent Frey syndrome. The total operating time, intraoperative blood loss, operating time after parotidectomy, and postoperative drainage volume were compared between the 2 groups. Results: The operating time after parotidectomy was significantly shorter in the PGA felt group than in the SCMF group (43.7 ± 10.7 vs 57.8 ± 15.7 minutes). The total operative time was shorter and the drainage volume was smaller in the PGA felt group than those in the SCMF group without statistical significance (210.1 ± 43.4 vs 234.3 ± 52.7 minutes and 80.6 ± 36.8 vs 118.8 ± 83.9 mL). Neither Frey syndrome nor other major complications occurred in either group. Conclusions: Use of PGA felt successfully prevented Frey syndrome, while being technically simpler and more rapid compared with SCMF transfer.